Teacher-Students Interaction in EFL Classroom: A Study Using Flander Interaction Analysis Categories System (FIACS) - Supriadin; wattiheluw, Nurlaila; nurul layali, Baiq (PROSIDING SEMINAR NASIONAL KEGURUAN DAN PENDIDIKAN (SNKP), 2024)
The purpose of this study is to look into how teachers and students interact in the EFL classroom. The study was conducted at one of the senior high schools in Indonesia, namely SMA I Monta. This research used a descriptive qualitative research method. The data was analyzed using the Flander Interaction Analysis Categories System (FIACS) to explore the percentage of discussion time between teacher and students during the teaching and learning process. This study's participants include one English teacher and 28 students, 10 of whom are males and 18 of whom are females. The data were collected by monitoring the class 3 meetings with a video recorder, audio recorder, and observation checklist. As shown in this study, students talk more extensively than the teacher talk during the classroom interaction. Based on the results of classroom observation, it was found that in the first meeting, 45.6% of verbal behavior done inside the classroom was student talk. Then, 48.96% was spent by teacher talk verbal behavior, both direct and indirect talk. In the second meeting, 53% of verbal behavior done inside the classroom was student talk, while the English teacher talk only 41.07% in both direct and indirect talk. In the third meeting, students talk increased with a percentage of 53.33%, while the teacher talk only 40.42%. From the three meetings of classroom interaction, the average of students talk was 50.64%, teacher talk was 43.48%, and silence or confusion was 5.84%. Therefore, it can be concluded that students talk is more dominant in verbal classroom interaction than the teacher talk in the context of EFL classroom.